Differential effects of enriched environment at work on cognitive decline in old age. - Then, F. S.; Luck, T.; Luppa, M.; Konig, H. H.; Angermeyer, M. C.; Riedel-Heller, S. G. (Neurology, 2015)
OBJECTIVES: The aim of the present study was to investigate how different mentally demanding work conditions during the professional life-i.e., enriched environments at work-might influence the rate of cognitive decline in old age. METHODS: Individuals (n = 1,054) of the Leipzig Longitudinal Study of the Aged, a representative population-based cohort study of individuals aged 75 years and older, underwent cognitive testing via the Mini-Mental State Examination (MMSE) in up to 6 measurement waves. Type and level of mentally demanding work conditions in the participants' former professional life were classified based on the O*NET job descriptor database. RESULTS: In multivariate mixed-model analyses (controlling for sociodemographic and health-related factors), a high level of mentally demanding work tasks stimulating verbal intelligence was significantly associated with a better cognitive functioning at baseline (on average 5 MMSE points higher) as well as a lower rate of cognitive decline (on average 2 MMSE points less) over the 8-year follow-up period compared with a low level. The rate of cognitive decline in old age was also significantly lower (on average 3 MMSE points less) in individuals who had a high level of mentally demanding work tasks stimulating executive functions than those who had a low level. CONCLUSIONS: The results suggest that a professional life enriched with work tasks stimulating verbal intelligence and executive functions may help to sustain a good cognitive functioning in old age (75+ years). The findings thus emphasize that today's challenging work conditions may also promote positive health effects.
Keywords: Aged; Aged, 80 and over; Cognition Disorders/*epidemiology; *Disease Progression; Executive Function/physiology; Female; Germany/epidemiology; Humans; Intelligence/physiology; Longitudinal Studies; Male; Occupations/*statistics & numerical data; Social Environment; Work/*statistics & numerical data